2013
DOI: 10.3390/cells2010057
|View full text |Cite
|
Sign up to set email alerts
|

Functional Assessment of Pharmacological Telomerase Activators in Human T Cells

Abstract: Telomeres are structures at the ends of chromosomes that shorten during cell division and eventually signal an irreversible state of growth arrest known as cellular senescence. To delay this cellular aging, human T cells, which are critical in the immune control over infections and cancer, activate the enzyme telomerase, which binds and extends the telomeres. Several different extracts from the Astragalus membranaceus root have been documented to activate telomerase activity in human T cells. The objective of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 21 publications
0
32
0
1
Order By: Relevance
“…Counteracting telomere attrition and its consequences has been a main target for research during the last decade [7,22]. Regenerative medicine has also focused on strategies to maintain telomere length [31]. Androgens, such as danazol, have been used to promote telomere elongation in patients with telomeropathies or telomere syndromes [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Counteracting telomere attrition and its consequences has been a main target for research during the last decade [7,22]. Regenerative medicine has also focused on strategies to maintain telomere length [31]. Androgens, such as danazol, have been used to promote telomere elongation in patients with telomeropathies or telomere syndromes [21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their antioxidant, anti-inflammatory, immunoregulatory and anticancer effects, extracts of Astragalus spp. have been shown to exert beneficial effects on telomeres and to stimulate telomerase activity in various models [22,23,31]. Most studies investigated cycloastragenol (TA-65), a single chemical entity isolated by a proprietary purification process from a root extract of Astragalus membranaceus [22,24,25,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…The potential to reactivate telomerase in somatic cells has shown promise to prevent senescence and increase lifespan. A natural plant compound called cycloastragenol [ 28 ] isolated from the roots of Astragalus membranaceus (a plant used as a tonic in TCM) has been reported to activate telomerase in cultured human CD4 + and CD8 + T lymphocytes . Cycloastragenol delayed telomere shortening, increased replicative capacity, and improved immune function in cultured CD8 + T lymphocytes isolated from human immunodeficiency virus‐positive individuals .…”
Section: Mechanism Of Life Extension By Molecules Isolated From Plantmentioning
confidence: 99%
“…A natural plant compound called cycloastragenol [28] isolated from the roots of Astragalus membranaceus (a plant used as a tonic in TCM) has been reported to activate telomerase in cultured human CD4 + and CD8 + T lymphocytes. [210][211][212] Cycloastragenol delayed telomere shortening, increased replicative capacity, and improved immune function in cultured CD8 + T lymphocytes isolated from human immunodeficiency virus-positive individuals. 213 In female mice, cycloastragenol, also called TA-65, increased telomere length in some tissues, most notably in the liver, and improved some healthspan indicators including glucose tolerance, osteoporosis, and skin aging but no lifespan increase was observed.…”
Section: Telomerase Activationmentioning
confidence: 99%
“…49 Research continues in using cycloastragenol from the Astragalus plant that has been shown in one study to activate telomerase. 50 Telomerase activators have suggested a slowing of aging in mice. 51,52 Other studies on affecting telomeres and increasing protective telomerase continue including lifestyle and dietary factors.…”
Section: Telomeresmentioning
confidence: 99%